The Axiology of Waqf in Islamic Education: A Hermeneutic Analysis of Junaid Thola's Thought - Nasution, Marlian Arif; Ikbal, Muhammad; Rahmat, Paisal (Al-Hayat: Journal of Islamic Education, 2026)
The limited capacity of pesantren to develop Islamic education oriented toward institutional self-reliance in Mandailing Natal indicates an axiological problem in the management of waqf as a value-based instrument of education. In this context, the thought of Junaid Thola offers a historical–contextual perspective on waqf as the axiological foundation of Islamic education. This study aims to examine the relevance of Junaid Thola’s thought in Kaifiyyat (1927) as a basis for developing an Islamic education model grounded in Pesantrenpreneurship and productive waqf. The researchers employed a qualitative methodology with a multiple-case study design and conducted the study in six pesantren in Mandailing Natal (Musthafawiyah, Al-Junaidiyah, Darul Ikhlas, Darul Ulum, Darul Hadis, and Roihanul Jannah). A constructivist–interpretive approach is integrated with hermeneutic analysis to explore the relationship between classical Islamic texts and contemporary pesantren educational practices. The researchers collected data through in-depth interviews, observations, and document analysis and analysed them using interactive and abductive techniques supported by triangulation. The findings reveal that the relevance of Junaid Thola's thought within the context of pesantren-based Islamic education varies across institutions. Very high relevance is observed in pesantren with extensive waqf asset bases, whereas moderate relevance is found in pesantren with limited educational economic business units. Factors strengthening relevance include the availability of waqf assets and the coherence of leadership values with Islamic educational and business ethics, while limitations in physical assets function as constraining factors. Hermeneutic analysis of Kaifiyyat (1927) identifies 88 practical approaches to productive waqf encompassing six primary asset sources (agriculture, infrastructure, commerce, vocational activities, zakat, and collective contributions). These findings are synthesised into a Three-Pillar Axiological Model of Islamic Education, consisting of pesantren economic self-reliance (Asset Ontology), Islamic character education (Ethical Axiology), and Institutional Sustainability (Managerial Epistemology). This study contributes to the development of an integrative pesantren-based Islamic education model that bridges classical waqf thought with contemporary entrepreneurship-oriented educational practices.